Safety of pulsed-field ablation in patients with cardiac implantable electronic devices. A single-center pilot study. (19th May 2022) - Winkelmann, SJ; Lemoine, MD; Wuerger, T; Schleberger, R; Rottner, L; Dinshaw, L; Moser, JM; Muenkler, P; Nikorowitsch, J; Reissmann, B; Ouyang, F; Toennis, T; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Pulsed-field ablation (PFA) is a novel energy source to perform pulmonary vein isolation (PVI) in patients with atrial fibrillation or cavo-tricuspid isthmus ablation (CTI) in patients with atrial flutter. Whether strong electrical fields generated by PFA could change the function and integrity of cardiac implantable electronic devices (CIED) is not known. Aim: To assess the function and integrity of implanted devices before and after pulsed-field ablation. Methods: This study included consecutive patients with CIED undergoing PFA at a large single center. Real-time CIED electrograms were recorded during PFA applications. CIED were interrogated before and after PFA assessing function (threshold, sensing), integrity (impedance), and arrhythmia episodes. Results: We performed PFA in six patients (age 69±12 years, 1/6 female, left atrial diameter was 44±3 mm, left-ventricular ejection fraction 40±14%) for PVI in five patients with atrial fibrillation and CTI ablation in one patient with atrial flutter. All patients had CIEDs (one cardiac resynchronization device, two implantable cardioverter-defibrillators, three two-chamber pacemakers). Each patient undergoing PVI received 32 PFA applications of 2.5 s. (4x basket configuration and 4x flower configuration at each pulmonary vein), amounting to a total ablation time of 80 s and resulting in complete PVI in all five patients. For CTI ablation we applied 8 PFA applications of 2.5 s (20 s total ablation time) resulting in CTI blockade. Real-time intracardiac electrograms (iEGM) during PFA applications revealed sensing of single PFA application impulses in three patients and blanking of the iEGM in three patients. Postinterventional device testing revealed no changes in impedance, stimulation threshold or sensing. No leads were dislocated or damaged. No other device malfunctions occurred during the procedure, as well as no other major periprocedural complications occurred. Conclusion: The function and integrity of pacemakers and defibrillators is not affected by PFA in our patient sample. Larger series are needed to confirm the apparent safety of PFA in patients with CIED.